Moral Values And The Upbringing Of Youth - Tulanov Mamasidiq (Zien Journals, 2025)
This article is about increasing orrortunities for intercultural communication in the country and region as a whole, in the context of increasing the orrortunities for cultural communication and today, in the context of innnovation, intellectual Oriental Renaissance.
Keywords: youth; culture; cultural image; universal values